Chamaepinnularia attenboroughiana, a new diatom species from the Antarctic Continent (Sellaphoraceae, Bacillariophyceae) - Buffoli, Marina; Verleyen, Elie; Badnal, Mahesh; Sabbe, Koen; Vijver, Bart Van De (Phytotaxa, 2026)
A new species in the genus Chamaepinnularia is described from the Antarctic Continent based on the unique presence of a shallow longitudinal groove bordering the raphe from apex to central area. The new species, Chamaepinnularia attenboroughiana, is further characterised by its lanceolate valve outline, slightly deflected, gradually inflated central raphe endings and small central area forming a subfascia. The species was observed in several layers of a sediment core of Progress Lake, Larsemann Hills, East-Antarctica.